2021
DOI: 10.23939/chcht15.01.142
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Initiators on the Adhesion Properties of Bitumen Modified by Natural Origin Epoxide

Abstract: The article is presenting a modification of bituminous binder with ecological epoxidized rapeseed oil (BERO) in the presence of the initiator (hardener). Adipic acid (AA), maleic anhydride (MA) and polyethylene polyamine (PEPA) were used as the initiators. The effect of modification temperature and, as well as initiator nature, on the bitumen properties was determined. Bitumen modified with BERO was evaluated by the following indicators: softening temperature, penetration, ductility, and adhesion to the glass.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 16 publications
0
5
0
3
Order By: Relevance
“…Традиційний немодифікований асфальтобетон не може забезпечити фізико-механічні властивості покриття, необхідні для їх довговічної експлуатації [2,5,6,7,13,16]. Властивості бітуму, як компонента асфальтобетону, є найчутливішими до впливу перерахованих вище чинників.…”
Section: вступunclassified
See 2 more Smart Citations
“…Традиційний немодифікований асфальтобетон не може забезпечити фізико-механічні властивості покриття, необхідні для їх довговічної експлуатації [2,5,6,7,13,16]. Властивості бітуму, як компонента асфальтобетону, є найчутливішими до впливу перерахованих вище чинників.…”
Section: вступunclassified
“…Ефективність BERО, як модифікатора бітумів, було встановлено у попередніх дослідженнях [8,9,13]. Для підтвердження позитивного впливу BERО на адгезійні властивості модифікованого бітуму, порівнювали основні характеристики вихідного бітуму та бітуму, модифікованого BERО.…”
Section: аналіз останніх досліджень та публікаційunclassified
See 1 more Smart Citation
“…In previous works [1,6,7] it was found that the modification of road bitumens BERO, allows to improve the quality characteristics of road bitumens, such as adhesion, penetration, softening temperature [1,6,7]. At the same time adhesion improves 3 times both to a stone, and to glass.…”
Section: Introductionmentioning
confidence: 99%
“…Bitumens, in turn, are modified in every way to obtain a better road surface. Among the many additives [1][2][3][4][5][6][7][8][9][10][11] that improve the quality of bitumen and asphalt concrete, known polymers, adhesion promoters, fibers, waxes, rubber crumb, natural bitumen, the most popular modifiers are polymers. They are also divided into thermoplastics, thermoplastics, terpolymers and latexes.…”
Section: Introductionmentioning
confidence: 99%